Investigation of petrophysical and hydrogeological parameters of the transboundary Nubian Aquifer system using geophysical methods - Mohammed, Musaab A. A.; Mohamed, Ahmed; Szabó, Norbert P.; Alarifi, Saad S.; Abdelrady, Ahmed; Alao, Joseph Omeiza; Szűcs, Péter (Frontiers in Earth Science, 2024)
The recent research aims to investigate the petrophysical and hydrogeological parameters of the Nubian aquifer system (NAS) in Northern Khartoum State, Sudan, using integrated geophysical methods, including surface electrical resistivity and geophysical well-logging. The Nubian aquifer is a transboundary regional aquifer that covers vast areas in Sudan, Egypt, Libya and Chad. The well-logs, including self-potential (SP), natural gamma ray (GR), and long normal resistivity (RS), are integrated with Vertical Electrical Sounding (VES) measurements to delineate the hydrostratigraphical units. As a result, two aquifers are detected. An upper aquifer comprises coarse sand with an average thickness of 50 m and a lower aquifer of sandstone with more than 200 m thickness. For a thorough evaluation of the aquifers, in the first stage, the petrophysical and hydrogeological parameters, including formation factor, total and effective porosity, shale volume, hydraulic conductivity, and transmissivity, are measured solely from geophysical well-logs.In the second step, the results of geophysical well logs are combined with VES and pumping test data to detect the spatial variation of the measured parameters over the study area. As a result, the hydraulic conductivity of the Nubian aquifers ranged from 1.9 to 7.8 m/day, while the transmissivity varied between 120 and 733 m 2 /day. These results indicated that the potentiality of the Nubian formation is high; however, in some regions, due to the sediment heterogeneity, the aquifers have intermediate to high potential.According to the obtained results, it can be concluded that the Nubian Aquifer in Khartoum state is ideal for groundwater development. This research discovered that geophysical approaches can be used to characterize moderately heterogeneous groundwater systems by comparing the Nubian aquifer with similar aquifer systems that have similar hydrogeological settings. This study emphasized the application of universal principles in extrapolating hydraulic parameters in hydrogeophysical surveys. This approach aims to reduce the costs and efforts associated with traditional hydrogeological approaches.